2013
DOI: 10.5005/jp-journals-10006-1244
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Practice of Contraception among Gynecologists at a Tertiary Care Hospital

Abstract: Medical healthcare providers are an important link with the general public to impart knowledge regarding contraception. However, their own attitude and practice of contraception is often lacking.Objective: This study was conducted to assess the attitude and practice of contraception over the last 5 years of the gynecologists themselves in a tertiary care hospital in Jaipur. Materials and methods:The study was conducted on 125 female gynecologists in a tertiary care hospital in Jaipur. All were given a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This was higher than 51% reported in the general population by Patel et al [13], 59% in rural Haryana by Choudhary et al [14] or 52.6% by Umoh et al in a study from Nigeria [9] despite having similar high knowledge scores. Himani et al evaluated the contraceptive practices of gynaecologist and observed that despite having complete knowledge about contraception, their own attitude and practices were lacking [15]. This bridge needs to be filled to achieve our family planning goals.…”
Section: Discussionmentioning
confidence: 99%
“…This was higher than 51% reported in the general population by Patel et al [13], 59% in rural Haryana by Choudhary et al [14] or 52.6% by Umoh et al in a study from Nigeria [9] despite having similar high knowledge scores. Himani et al evaluated the contraceptive practices of gynaecologist and observed that despite having complete knowledge about contraception, their own attitude and practices were lacking [15]. This bridge needs to be filled to achieve our family planning goals.…”
Section: Discussionmentioning
confidence: 99%